2014
DOI: 10.1038/eye.2014.163
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed vs continuous light accelerated corneal collagen crosslinking: in vivo qualitative investigation by confocal microscopy and corneal OCT

Abstract: Purpose To assess qualitative corneal changes and penetration of pulsed and continuous light accelerated crosslinking by in vivo confocal microscopy and corneal OCT. Methods A total of 20 patients affected from progressive keratoconus were enrolled in the study. Ten eyes of 10 patients underwent an epithelium-off pulsed-light accelerated corneal collagen crosslinking (PL-ACXL) by the KXL UV-A source (Avedro Inc.) with 8 min (1 s on/1 s off) of UV-A exposure at 30 mW/cm 2 and energy dose of 7.2 J/cm 2 ; 10 eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 30 publications
(31 reference statements)
5
84
3
1
Order By: Relevance
“…This is consistent with the findings reported in other series evaluating the results of transepithelial CXL, either by iontophoresis or accelerated. [19][20][21][22][23][24][25][26][27] Similarly, in line with all previous studies on transepithelial CXL, 19-27 a significant improvement in CDVA was observed after surgery that remained throughout the entire 12-month follow-up period. Lesniak and Hersh,24 in a prospective study, evaluated a similar technique and found a mean improvement in CDVA of 0.83 Snellen lines.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is consistent with the findings reported in other series evaluating the results of transepithelial CXL, either by iontophoresis or accelerated. [19][20][21][22][23][24][25][26][27] Similarly, in line with all previous studies on transepithelial CXL, 19-27 a significant improvement in CDVA was observed after surgery that remained throughout the entire 12-month follow-up period. Lesniak and Hersh,24 in a prospective study, evaluated a similar technique and found a mean improvement in CDVA of 0.83 Snellen lines.…”
Section: Discussionsupporting
confidence: 76%
“…Other studies have evaluated changes in the maximum keratometry after different modalities of transepithelial CXL. [19][20][21][22][23][24][25][26][27] Lesniak and Hersh 24 found a mean reduction of 0.9D in the maximum keratometry in a prospective study that evaluated the results of a similar CXL technique than that used in our study over a 6-month period. It should be borne in mind that this study included keratoconus cases that were more advanced than in our series, so the mean keratometry was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,26 2) 20 underwent high-fluence epithelium-off accelerated crosslinking (ACXL) at 30mW/cm 2 (10 eyes with pulsed light and 10 eyes with continuous light UV-A exposure). 15,16 3) 10 underwent transepithelial crosslinking (TE-CXL) at 3mw/cm 2 . 36 4) 10 underwent transepithelial accelerated crosslinking (TE-ACXL) at 45 mW/cm 2 .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…12 However, clinical and experimental evidence did not show significant differences between the pulsed and standard CXL protocol. [13][14][15] These unsuccessful implementations show that there is a need for a better understanding of the cellular and molecular events occurring during CXL.…”
mentioning
confidence: 99%